The global, regional, and national prostate cancer burden and trends from 1990 to 2021, results from the global burden of disease study 2021 - Liu, Xiaomu; Jiang, Haiou (Frontiers in Public Health, 2025)
BackgroundThe rising annual incidence of prostate cancer (PCa) has become a significant health challenge for men worldwide. The study aims to estimate the contemporary disease burden of PCa across global, regional, and national levels.MethodsData from the Global Burden of Disease Study 2021 (GBD 2021) was analyzed to evaluate trends in PCa incidence, prevalence, disability-adjusted life years (DALYs), and mortality from 1990 to 2021. Determinants of PCa burden were investigated through Spearman correlation analysis with socio-demographic index (SDI), decomposition analysis, and frontier analysis to assess regional improvement potential.ResultsIn 2021, global PCa incidence reached 1.32 million cases [95% uncertainty interval (UI): 1217320.93, 1400222.17]. Between 1990 and 2021, the global estimated annual percentage change (EAPC) of age-standardized incidence rates (ASIR), prevalence rates (ASPR), DALYs rates (ASDR), and mortality rates (ASMR) were declined or increased at −0.06% [95% confidence interval (CI): −0.21, 0.08], 0.42% (95% CI: 0.26, 0.58), −0.96% (95% CI: −1.05, −0.87), and −0.58% (95% CI: −0.73, −0.44), respectively. Low-middle SDI countries exhibited the steepest rate increases, with males over 50 years being most affected. Significant positive correlations emerged between SDI levels and ASIR (R = 0.543, p < 0.001) or ASPR (R = 0.709, p < 0.001), whereas EAPC of ASDR (R = −0.430, p < 0.001) or ASMR (R = −0.450, p < 0.001) inversely correlated with SDI among 204 countries and territories. Decomposition analysis revealed the global increase of DALYs for PCa was predominantly attributed to aging (77.65%) and population growth (58.59%). Frontier analysis identified substantial improvement potential across development spectra, particularly in middle to high SDI regions.ConclusionOur findings demonstrated that despite modest declines in ASDR and ASMR within high SDI regions, PCa burden metrics persistently increased in low-middle SDI quintiles. Nations across all development levels require urgent implementation of evidence-based policies and precision management strategies to mitigate this growing public health challenge.